The M/V "Norstar" Case (Panama v. Italy) (ITLOS). (August 2019) - Collins, Richard
Abstract : On April 10, 2019, the International Tribunal of the Sea (ITLOS) gave judgment in the M/V "Norstar" (Panama v. Italy) case. This was the first time an international tribunal had ruled directly on the principle of freedom of navigation in international waters. Specifically, ITLOS found (by fifteen votes to seven) that by arresting and detaining the Panamanian-flagged M/V "Norstar", Italy had violated Article 87(1) of the 1982 UN Convention on the Law of the Sea (UNCLOS). In doing so, the Tribunal arguably relied on a quite expansive understanding of the exclusive flag state jurisdiction principle as set out in Article 92 UNCLOS—a point that was argued forcefully in a seven-judge dissenting opinion. Below, I will briefly outline the background to the case before setting out the central aspects of the judgment and considering further this point of contention surrounding the permissibility of nonflag prescriptive measures in international waters.